Kyiv Meridian Axial Circle Catalogue (KMAC1) of stars in fields with extragalactic radio sources - Babenko, Yu.; Lazorenko, P.; Karbovsky, V.; Buromsky, M.; Kasjan, S.; Denysyuk, O. (Кинематика и физика небесных тел, 2005)
The catalogue of astrometric (positions, proper motions) and photometric (B, V , R, r', J) data of stars in 192 fields with the ICRF objects has been compiled at the Main Astronomical Observatory of the National Academy of Sciences of Ukraine and the Astronomical Observatory of the Kyiv National University. All fields are located in declination zone from 0° up to +30° ; a nominal field size is 46' (right ascension)×24' (declination). The observational basis of this work is 1100 CCD scans deep to V =17 mag which were obtained with the Kyiv Meridian Axial Circle in 2001–2003 and which contain one million of images. Coordinates of star image centroids have been computed both as the weighted centers of gravity and as the linearized Gaussian profile fitting with unequal weights. Astrometric reductions have included corrections depending on image size fluctuations and position of a star on the CCD frame on the declination axis. A special approach was used for correction of magnitude-dependent errors since images of bright stars were oversaturated. The KMAC1 catalogue is presented in two versions. The KMAC1–T version contains 159 fields (104 796 stars) and was obtained with reduction to the Tycho-2 catalogue. For another 33 fields, the reduction was found to be unreliable due to a low sky density of the Tycho-2 stars. Therefore, transformation the second version of the KMAC1–CU to the ICRF was derived using the UCAC2 and CAMC13 catalogues as reference ones; it contains 115 032 stars in 192 fields and is of slightly better accuracy. As compared with the first version proper motions were derived using the USNOA2.0 catalogue as a first epoch catalogue. An external accuracy (based on comparison with UCAC2 and CMC13) of one catalogue position is about 60–70 mas for 14–15 mag stars. An average value of photometry error is better than 0.1 mag for stars to 16 mag.